INFLUENCE OF COMPLEX OF PREPARATIONS ON THE STATE OF THE ORAL CAVITY TISSUES IN RATS UNDER THE CONDITIONS OF EXPERIMENTAL HYPOTHYROIDISM - Ivanov, V.S.; Tkachenko, Ye.K.; Shnaider, S.A.; Shvartsnau, O.H.; Dorosh, I.V.; Jenčova, J.; Petrašova, A. (World of Medicine and Biology, 2022)
The research is dedicated to studying the state of the dentoalveolar system and tissues of the oral cavity of rats under the influence of the complex under the action of experimental hypothyroidism. Experimental hypothyroidism was simulated in 8 1-month-old rats (group 2). The intact group (group 1) consisted of 8 rats. 7 rats received a complex under conditions of experimental hypothyroidism (group 3). The duration of the study was 30 days. The complex of preparations in conditions of insufficiency showed a significant caries-preventive and periodontal-protective effect. Under the action of the complex, an increase in the activity of alkaline phosphatase in the periodontal bone tissue and dental pulp was revealed, as well as a decrease in the activity of acid phosphatase in the bone of the alveolar process.